Pengaruh Kreativitas dan Inovasi dalam Desain Grafis sebagai Pendukung Branding UMKM - Nurbadillah, Nurbadillah; Wiguna, Indra Maki; Fadlurohman, Rizky; Kuntari, Wien; Nurbadillah (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
Graphic design is very important for helping the branding of Micro, Small, and Medium Enterprises (MSMEs), especially in today's competitive digital world. This study aims to look at how creativity and innovation in graphic design affect the success of MSMEs branding. Using a quantitative method, data was gathered through a survey with a Likert-scale-based questionnaire from 25 MSMEs owners in the food, fashion, and craft industries in the Greater Jakarta area (Jabodetabek). The analysis methods used are descriptive analysis and multiple linear regression to assess the link between creativity and innovation in graphic design and branding success. The findings show that graphic design aspects like logos, packaging, and creative promotional visuals can boost product attractiveness (84%), build a solid brand image (86%), and encourage customer loyalty (82%). Participants also mentioned that graphic design plays a key role in increasing the competitiveness of MSMEs in the market (86%). However, limited access to technology and design software (74%) is a significant obstacle that must be tackled. This research shows that graphic design is not just about looks but is also a strategic tool in branding that can strengthen brand identity and help with product marketing. To make better use of graphic design, suggested actions include enhancing access to technology, educating MSMEs owners on branding and graphic design, and working with professional designers. This study gives useful suggestions for MSMEs to implement more creative and innovative branding strategies to boost their competitiveness in a constantly changing market.